Dielectric and thermal properties characterisation and evaluation of novel epoxy materials for high‐voltage power module packaging - Zhengdong Wang; Ganqiu Yang; Xiaolong Cao; Mengli Li; Tong Zhang; Chenxin Liu; Yuanhang Zhou; Yonghong Cheng (High Voltage, 2024)
Abstract Internal insulation of high‐voltage power modules is facing interesting failure risks, including high temperature overheating, breakdown fault, material cracking etc., so it is imperative to urgently develop new dielectric materials with high thermal conductivity (λ), outstanding electrical insulation, and thermal stability properties. A method to construct controllable liquid crystalline cross‐linking networks based on the synthesis of biphenyl epoxy monomer and the change of curing agent structures and curing temperature is proposed. The uniform nematic rod‐like liquid crystalline domains were obtained by using 4,4‐diaminodiphenylmethane as a curing agent under a pre‐curing temperature of 105°C. The resulting film (abbreviated as TD‐105) exhibited λ up to 0.53 W m−1 K−1 and a dielectric breakdown strength of 57.69 kV mm−1, which showed a simultaneous enhancement of 178% and 16%, respectively, compared to traditional bisphenol A epoxy resin. Moreover, it also exhibited lower dielectric loss and magnitude of partial discharge while having higher glass‐transition temperature (190°C). A novel idea for the development of high‐performance epoxy insulating materials for the application of high‐voltage and large‐power electrical equipment is provided.